Retinal Degeneration After First-Ever Optic Neuritis Helps Differentiate Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder - Kim, Nam-Hee; Kim, Ho Jin; Park, Cheol-Yong; Jeong, Kyoung Sook (Frontiers in Neurology, 2019)
Objective: Differentiation between neuromyelitis optica spectrum disorder (NMOSD) and multiple sclerosis (MS) in the early phase is challenging but crucial for treatment and prognosis. Methods: We performed a prospective cross-sectional study to discriminate NMOSD from MS by evaluating retinal degeneration in optical coherence tomography (OCT) after a first-ever optic neuritis (ON) episode. Seventy-three NMOSD patients and thirty-eight MS patients with ON at least three months prior were assessed by OCT, best-corrected visual acuity (VA), and 2.5% low-contrast VA. Multivariate linear regression models were used for comparisons. Receiver operating characteristic curves and Youden index were used for determining the discriminative value of retinal nerve fiber layer thickness (RNFL) and VA in distinguishing NMOSD from MS. Results: Among eyes with retinal degeneration after a first-ever ON episode (n=93), NMOSD eyes (n=60) presented thinner RNFL (p<0.001) and worsened VA (p<0.001) relative to MS eyes (n=33). Furthermore, a RNFL thinner than 78.9 µm had a specificity of 93.9% for NMOSD; combined with a VA of less than 0.4 decimal, these characteristics provided 100% specificity for NMOSD. Conclusions: The first-ever ON eyes showed more severe retina degeneration in patients with NMOSD than MS, which could establish a cut-off of RNFL thickness and VA to distinguish NMOSD from MS in the early phase.